Procedures for Evaluating Learning Outcomes of Islamic Education - Amalia, Amalia; Muslimah, Muslimah (Bulletin of Science Education, 2021)
This study is motivated by the fact that decisions have a very important importance in the teaching and learning process. If learning has an important role in educating students both in terrms of cognitive, affective and psychomotor, then function evaluation as away of obtaining information to assess learning success is needed. Without evaluation activities, educators will find it dificult to find information about the advantages and disadvantages of the learning activities that have been implemented. This article uses the library research method (library research). The results of the study concluded from the results of the evaluation of PAI; collecting data; perform data levers; processing ang analizyzing data; interpreting or interpreting and drawing; and following results. Keywords: Procedures Evaluation, learning Outcome Islamic Education